2013
DOI: 10.2174/0929867311320190005
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish As a Genetic Model in Pre-Clinical Drug Testing and Screening

Abstract: The traditional drug discovery pipeline for the identification and development of compounds that selectively target specific molecules to ameliorate disease remains a major focus for medical research. However, the zebrafish is increasingly providing alternative strategies for various components of this pipeline. Zebrafish and their embryos are small, easily accessible and relatively low cost, making them applicable to high-throughput, small molecule screening. Zebrafish can also be manipulated by a range of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…Clearly, zebrafish also provides an inexpensive whole-animal vertebrate model for screening a library of small molecules, cell-or tissue receptorspecific compounds against viral pathogens or anti-angiogenic or anti-inflammatory compounds. 24,[46][47][48][49] One study has already employed this model to confirm the antiviral effect of acyclovir using HSV-1 infected zebrafish. 21 Ideally, zebrafish in a 96-well format can be treated with antibodies 50 or compounds targeting specific cells/tissues or modified antiviral peptides with an objective to have higher efficacy.…”
Section: Zebrafish Model: Overall Advantages To Study Viral Infectionsmentioning
confidence: 99%
“…Clearly, zebrafish also provides an inexpensive whole-animal vertebrate model for screening a library of small molecules, cell-or tissue receptorspecific compounds against viral pathogens or anti-angiogenic or anti-inflammatory compounds. 24,[46][47][48][49] One study has already employed this model to confirm the antiviral effect of acyclovir using HSV-1 infected zebrafish. 21 Ideally, zebrafish in a 96-well format can be treated with antibodies 50 or compounds targeting specific cells/tissues or modified antiviral peptides with an objective to have higher efficacy.…”
Section: Zebrafish Model: Overall Advantages To Study Viral Infectionsmentioning
confidence: 99%
“…The extra-uterine development of hundreds of eggs also permits a greater number of studies in genetically identical organisms. Since the first reported xenotransplantation of human cells into zebrafish ( Lee et al , 2005), many laboratories have shown that zebrafish embryos are useful for the study of other facets of tumour biology including cancer-induced angiogenesis ( Haldi et al , 2006); cancer cell invasion and metastasis ( de Boeck et al , 2016; Marques et al , 2009); cancer stem cell growth ( Bansal et al , 2014; Chen et al , 2017); interaction of cancer cells with the host ( Feng & Martin, 2015); and drug screening ( Corkery et al , 2011; Gibert et al , 2013). Importantly, the development of human tumours and their response to chemotherapeutic treatment in zebrafish embryos is comparable to that observed in mouse xenograft assays ( Fior et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The average length of an adult fish is at 2 to 4 cm, accessible for relatively low-cost and high-throughput small molecule screening[9]. Their physiological complexity also provides conserved models of human disease for in vivo validation studies[10].…”
Section: Introductionmentioning
confidence: 99%